Teamwork: relevance and interdependence of interprofessional education - M Tamayo; A Besoaín-Saldaña; M Aguirre; J Leiva
ABSTRACT OBJECTIVE Determine the perception of university students regarding interprofessional and interdependent work between team members in their inclusion in primary care. METHODS Analytical cross-sectional study. The sampling had a probabilistic, stratified random type with 95% confidence and 5% margin of error. Seven-hundred and four students of Public Universities in Santiago (Chile) answered self-administered questionnaire. RESULTS Ninety-seven point eight of students say that interprofessional work is important; 27.1% of them declare that their university did not seem to show that their study plans were important. The professionals listed as most important in teams are physicians and nurses. CONCLUSIONS Spaces for development and institutional support are key elements to promote interprofessional work. If this competence can involve each academic unit in their different formative spaces there will be a significant contribution to said promotion. Teamwork is a pending task.